Flavonoids and Antioxidant Activities of Silver Nanoparticles of Extract Galaxaura rugosa - Savitri, Evika; Bahari, Mohamad Fajar; Minarno, Eko Budi; Shinta (Biota, 2025)
Algae Galaxaura rugosa contains phenolic compounds, flavonoids, β-carotene, and galactane sulfate, which are natural antioxidants. The development of antioxidants of red algae into silver nanoparticles (AgNPs) can improve their effectiveness in preventing ROS. The objective of this study is to synthesize silver nanoparticles using G. rugosa algae as well as to test the total flavonoid levels and antioxidant activity of G. rugosa silver nanoparticles. The method of research for synthesis silvernanoparticles using extract G. rugosa as a bioreductor. Characterization of silver nanoparticle G. rugosa using Particle Size Analysis (PSA) and UV-Vis Spectrophotometer. The total flavonoid and antioxidant activities of silver nanoparticles using UV- VIS spectrophotometer. The test of antioxidant activity using the DPPH method. The research results showed that silver nanoparticles using G. rugosa resulted in a color change of the soluble from green to yellow.  The UV- VIS spectrophotometer measurement in the 570-580 nm wave range with a maximum wavelength of 406 nm. The measurement of the size distribution of the nanoparticles formed using PSA is an average of 11 nm. Total flavonoid silver nanoparticles of G. rugosa value of 36.21±0.65 mgQE/g higher than extract value of 32,12±0,79 mgQE/g. The antioxidant activity of IC50 of silver nanoparticle G. rugosa value of 26.658 ±1.44 ppm is very strong and the extract value of 46,128 ± 1.6 is strong category.